Naukowe, polityczne i gospodarcze aspekty zainteresowania dziedzictwem kulturowym Kaszubów - Kwaśniewska, Anna (Studia Etnologiczne i Antropologiczne, 2014)
An important role of creating and maintaining identity of ethnic groups is a cultural heritage. That is an expression of the continuity of cultural, social and political. Contemporary interest of the cultural heritage of Kashubians and their language, stems from the process of creating a nation of Kashubian. System transformation and the associated with this a liberal economy contributed to the recovery of activity of local communities in various fields. It proved that globalization is a destructive force but also, strengthening local communities, that they realize the importance of their cultural heritage, solicit its preservation, on the other hand, treat as a commercial product.